2020
DOI: 10.1186/s13104-020-04988-5
|View full text |Cite
|
Sign up to set email alerts
|

Difference in autonomic nervous effect of blue light depending on the angle of incidence on the eye

Abstract: Objective: Blue light has been attributed to the adverse biological effects caused by the use of smartphones and tablet devices at night. However, it is not realistic to immediately avoid nighttime exposure to blue light in the lifestyle of modern society, so other effective methods should be investigated. Earlier studies reported that inferior retinal light exposure causes greater melatonin suppression than superior retinal exposure. We examined whether the autonomic responses to blue light depends on the ang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Natural blue light can regulate our sleep and wake cycles, boost alertness, modulate mood, etc., but prolonged exposure to blue light at night can disrupt circadian rhythm and can cause many additional health issues, such as diabetes, heart disease, and depression. Most importantly, it can cause permanent eye damage and age-related macular degradation, leading to vision loss (Figure d­(I)). …”
Section: Introductionmentioning
confidence: 99%
“…Natural blue light can regulate our sleep and wake cycles, boost alertness, modulate mood, etc., but prolonged exposure to blue light at night can disrupt circadian rhythm and can cause many additional health issues, such as diabetes, heart disease, and depression. Most importantly, it can cause permanent eye damage and age-related macular degradation, leading to vision loss (Figure d­(I)). …”
Section: Introductionmentioning
confidence: 99%
“…Glickman et al [ 45 ] also demonstrated that nighttime white light exposure to the inferior retina caused melatonin suppression, while exposure to the superior retina caused no significant suppression. In a previous study, we also investigated the effect of the angle of incidence on the autonomic effects of blue light and observed similar effects with light from directly above [ 31 ]. The present observations indicate that the biological effects of the non-imaging function of blue light could be regulated separately from the subjective comfort caused by the image-forming function by choosing different directions of light into the eye for ambient and task light.…”
Section: Discussionmentioning
confidence: 91%
“…The ambient lighting was designed to illuminate from a direction perpendicular to the subject's visual axis. In a previous study, we examined whether the autonomic responses to blue light depends on the angle of incidence to the eye in healthy subjects, but no significant difference was observed in autonomic indices of heart rate variability for a wide range of angles of incidence from -90° to +90° [ 31 ]. This suggests that the biological effects of the non-imaging function of blue light may be regulated separately from the subjective comfort at least that is caused by the image-forming function by choosing different directions of light into the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the small number of participants, it is hard to apply these results to the general population. Studying the consequences of blue light exposure at a systemic level may also require longer study periods than those used in Yuda et al’s studies [ 50 , 51 , 115 ]. This eliminates the possibility of a situation in which the systemic response to blue light may have not been fully saturated and may have progressed further than the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies have shown that blue light induces a sustained higher arousal and alertness state, these results should be interpreted with a great deal of caution, as baseline data was not collected and possible differences in autonomic (some also influenced by the menstrual cycle) and psychomotor performance cannot be firmly excluded. Starting from the idea that white light exposure to the inferior retina causes greater melatonin suppression when compared with exposure to the superior retina [ 116 , 117 ], Yuda et al investigated the autonomic effects of blue light emitted by OLEDs (chromaticity (x = 0.14, y = 0.16), 15.4 lx, MSPFD of 0.28 μmol/m 2 /s, relative MSPFD 75%) [ 115 ] and found no significant exposure angle-dependent effect on the autonomic indices of HRV.…”
Section: Discussionmentioning
confidence: 99%